Ultra-small CoOx/GO catalyst supported on ITO glass obtained by electrochemical post-treatment of a redox-active infinite coordination polymer: a portable reactor for real-time monitoring of catalytic oxidative degradation of colored wastewater. Issue 2 (8th January 2020) - You, Xinrui; Huang, Chunyu; Huang, Wei; Shi, Guoyue; Deng, Jingjing; Zhou, Tianshu
Abstract : Ultra-small CoO x /GO on ITO glass obtained by electrochemical polarization of a Co-ICP and its application in catalytic oxidative degradation of colored wastewater. Abstract : In this work, we have developed a novel method for preparing a CoO x /GO catalyst supported on ITO glass by electrochemical post-treatment of redox-active infinite coordination polymer (ICP) Co(3, 5-dbsq)(3, 5-dbcat)(bix) nanoparticles. Firstly, highly dispersed CoO x nanoparticles with ultra-small size and narrow size distribution (1.42 ± 0.34 nm) were in situ synthesized on ITO glass after electrochemical polarization of ICP coated on ITO glass at −1.1 V for 16.7 min (1000 s) in 0.10 mol L −1 KCl. Graphene oxide (GO) was next mixed with the ICP to obtain the CoO x /GO catalyst supported on ITO glass (the size of CoO x nanoparticles ranged within 1.21 ± 0.28 nm), which proved to have improved catalytic performance and enhanced stability compared to the pure CoO x . The catalytic activity of this CoO x /GO catalyst was then optimized according to the degradation efficiency of methylene blue (MB) via an advanced oxidation process in the presence of peroxymonosulfate (PMS). Under the optimal conditions here, the enhanced catalytic oxidative degradation of dye solution could be achieved easily. 100% of MB (2.0 mL, 20 mg L −1 ) could be decomposed within 6.7 min, which is better than other CoO x catalysts. With this kind of ITO glass as a component part, a portable reactor was constructed for the first time. Real-time monitoring of the catalytic degradation of colored wastewater from the textile and cosmetic industries was then achieved using this reactor directly by incorporating a UV/vis spectrometer, which is of great importance for information analysis and process control optimization during industrial wastewater treatment.